Інтенсифікація масоперенесення в екстрагуванні рослинних олій - Бандура, В. М.; Коляновська, Л. М. (НТУ "ХПІ", 2013)
В статье приведены данные исследования экстрагирования масла из рапса сорта «Чемпион» и сои сорта «Винничанка» растворителем спиртом с помощью микроволнового интенсификатора.

The article presents research data extracting oil from rapeseed varieties "Champion" and soybean varieties "Vinnichanka" alcohol solvent using microwave intensifiers.
Intensification mass transfer in extraction vegetable oils
Keywords: енергетичні затрати; мікрохвильовий інтенсифікатор; олієвмісний ріпак; токофероли